Noworodek - stan rozwoju fizycznego i trendy rozwojowe urodzeniowej masy ciała - Kaliszewska-Drozdowska, Maria Danuta (Polskie Towarzystwo Antropologiczne, 1992)
Having continued the research carried out in 1960 and 1970, the sample of 1620 newborns (762 girls and 858 boys) bom in 1986 in Poznan were examined. Measurments of: body mass (1), si length (2), head circumference(3) and chest circumference (4) as well as the values of indices (1/2,3/4) were shown in the tables and on the graphs.
Newborn - the state of the physical development and the developmental trends of body mass